2022
DOI: 10.1039/d2cc03510c
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired peptide stapling generates stable enzyme inhibitors

Abstract: Stapling of peptides renders them ideal drug candidates. We report a new peptide staple resembling the natural metabolite lanthionine ketenamine. The strategy is orthogonal to canonical amino acids, proceeds in...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“… 122 We reported a peptide staple inspired by the natural product lanthionine ketenamine. 123 This reaction between 1,2-aminothiols and α-bromopyruvates is a combination of cysteine alkylation and imine formation and allows for the use of various aliphatic or PEG-based linkers ( Scheme 4E ).…”
Section: Strategies For Peptide Macrocyclisationmentioning
confidence: 99%
“… 122 We reported a peptide staple inspired by the natural product lanthionine ketenamine. 123 This reaction between 1,2-aminothiols and α-bromopyruvates is a combination of cysteine alkylation and imine formation and allows for the use of various aliphatic or PEG-based linkers ( Scheme 4E ).…”
Section: Strategies For Peptide Macrocyclisationmentioning
confidence: 99%
“…15 More recently, the Nitsche group reported a method of peptide stapling resembling the lanthionine ketenimine, which utilized the reactivity of bromopyruvate and cysteine to obtain stapled peptides through a two-component reaction (Figure 1a). 16 On the contrary, the development of two-component reactions on native peptides is more challenging, as it requires high amino acid specificity and chemoselectivity, tolerating the diverse functionalities present on the unprotected peptides. To this end, chemoselective reactions for Lys/Lys, 17 Cys/Cys, 18 Met/ Met, 19 and Lys/Cys 20 have been developed.…”
mentioning
confidence: 99%
“…Many research groups have developed two-component peptide stapling methods based on either unnatural amino acids or natural amino acids. For example, Spring et al introduced azide groups into two ornithine side chains of the peptide to undergo a click reaction with a dialkynyl linker to obtain the stapled peptide . More recently, the Nitsche group reported a method of peptide stapling resembling the lanthionine ketenimine, which utilized the reactivity of bromopyruvate and cysteine to obtain stapled peptides through a two-component reaction (Figure a) . On the contrary, the development of two-component reactions on native peptides is more challenging, as it requires high amino acid specificity and chemoselectivity, tolerating the diverse functionalities present on the unprotected peptides.…”
mentioning
confidence: 99%
“…We have previously demonstrated that the linker length of cyclic peptides is an important parameter to optimize inhibition of ZiPro. 28,31 In summary, we present a bioorthogonal technique to cyclize peptides rapidly and selectively through intramolecular oxime formation. This process produces macrocyclic peptides in high purity and is fully amenable to automatization.…”
mentioning
confidence: 99%
“…These effects are likely related to higher constraint of 14b , resulting in a lower entropic barrier of binding to NS2B-NS3. We have previously demonstrated that the linker length of cyclic peptides is an important parameter to optimize inhibition of ZiPro. , …”
mentioning
confidence: 99%